SISTEM INFORMASI GEOGRAFIS UNTUK PEMETAAN POHON MANGROVE DI KOTA TERNATE DAN KOTA TIDORE - Asrul S. Salasa; Muhammad Ridha Albaar; Hairil Kurniadi Siradjuddin; Salkin Lutfi; Muhammad Fhadli; Ardi Salman; Muhammad Andika Darwis; Ikram Mustafa; M. Mulkan Mufti (INTI Nusa Mandiri, 2026)
The mangrove ecosystems in Ternate City and Tidore City are under pressure due to coastal land conversion, residential development, and other anthropogenic activities. The main problem in mangrove conservation efforts in both regions is the lack of an integrated spatial information system to accurately and easily document the location, type, and condition of mangrove vegetation. This study aims to develop a web-based Geographic Information System (GIS) for mapping and managing mangrove data as a supporting instrument for conservation decision-making. The novelty of this research lies in the integration of field coordinate data, mangrove species identification, visual documentation, and interactive spatial visualization in a single platform that can be used for continuous monitoring of mangrove conditions in Ternate City and Tidore City. The study was conducted at five observation locations: Rua, Gambesi, and Mangga Dua Villages in Ternate City and Rum Balibunga and Mafututu Villages in Tidore City. Data were obtained through field surveys using GPS, mangrove species identification, and field documentation, then processed using PHP, MySQL, JavaScript, and LeafletJS technologies. The results of the study indicate that the system is able to map the distribution of several mangrove species, namely Rhizophora apiculata, Rhizophora mucronata, Bruguiera gymnorrhiza, Bruguiera parviflora, Ceriops tagal, Avicennia marina, and Sonneratia alba accurately and in an integrated manner. Functional testing using the Black Box Testing method confirmed that all system features operated correctly with a 100% success rate.